High-Throughput and Untargeted Metabolic Profiling Revealed the Potential Effect and Mechanisms of Paeoniflorin in Young Asthmatic Rats - Wang, Dan; Zhao, Li; Hao, Zhiyan; Huang, Ying; Liao, Yang; Wang, Lingli; Zhang, Jinfeng; Cao, Shan; Liu, Lixiao (Frontiers in Pharmacology, 2022)
Paeoniflorin (PF) is a multi-target monoterpenoid glycoside, and possesses broad pharmacological functions, e.g., antiinflammation, anti-depression, anti-tumor, abirritation, neuroprotection, antioxidant, and enhancing cognitive and learning ability. Paeoniflorin has gained a large amount of attention for its effect on asthma disease as the growth rate of asthma that has increased in recent years. However, its mechanism of action on asthma is still unclear. In this study, we have explored the action mechanism of PF on asthma disease. Furthermore, high-throughput untargeted metabolic profiling of asthma was performed through ultraperformance liquid chromatography/electrospray ionization quadruple time-of-flight-high-definition mass spectrometry (UPLC/ESI-Q-TOF/HDMS) combined with pattern recognition approaches and pathway analysis. A total of 20 potential biomarkers were discovered by UPLC/MS urine metabolic profiling. The key pathways including the citrate cycle (TCA cycle), pyrimidine metabolism, pentose phosphate pathway, tyrosine metabolism and tryptophan metabolism were affected by PF. In conclusion, we have discovered metabolite biomarkers and revealed the therapeutic mechanism of PF on based on liquid chromatography coupled with mass spectrometry untargeted metabolomics. The untargeted metabolomics combined with UPLC-MS was used to explore the therapeutic mechanism and targets of PF for the treatment of asthma. In this study, metabolomics combined with UPLC-MS is integrated to explore the metabolic mechanism of PF in the treatment of asthma in rats and to reveal the potential targets, providing theoretical support for the study of the treatment of PF.